2016
DOI: 10.1002/2015jd024098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a large and very shallow lake on local summer precipitation over the Lake Taihu basin in China

Abstract: Lake Taihu is the third largest freshwater lake in China and is situated in the Middle and lower Yangtze River delta. It is characterized by its shallowness (~1.9 m), large area (~2338 km 2 ), and high turbidity in recent years. The lake's effect on local summer precipitation is first studied in this paper through the use of an atmosphere-lake coupled model. By enlarging the light extinction coefficient, modifying the radiation scheme, and setting the roughness length to constants, the coupled model after adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…During the past several years, many researchers have paid lots of attention to the lake-air interactions at various spatiotemporal scales (Bonan 1995;Hostetler et al 1993Hostetler et al , 1994Long et al 2007;Lofgren 1997). Results have shown that as one of the typical land categories, inland lakes can lead to the spatiotemporal heterogeneity of surface energy budgets, which can further affect the atmospheric circulations and the regional weather and climate (Alcott et al 2012;Bartunkova et al 2014;Yeager et al 2013;Gu et al 2016;Xiao et al 2016). For example, due to the large thermal inertia, the presence of lakes delays the autumn/nighttime (spring/daytime) cooling (warming) and therefore dampens the diurnal and seasonal variations of low-level temperature in the Canadian Shield (Gula and Peltier 2012;Martynov et al 2012;Notaro et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the past several years, many researchers have paid lots of attention to the lake-air interactions at various spatiotemporal scales (Bonan 1995;Hostetler et al 1993Hostetler et al , 1994Long et al 2007;Lofgren 1997). Results have shown that as one of the typical land categories, inland lakes can lead to the spatiotemporal heterogeneity of surface energy budgets, which can further affect the atmospheric circulations and the regional weather and climate (Alcott et al 2012;Bartunkova et al 2014;Yeager et al 2013;Gu et al 2016;Xiao et al 2016). For example, due to the large thermal inertia, the presence of lakes delays the autumn/nighttime (spring/daytime) cooling (warming) and therefore dampens the diurnal and seasonal variations of low-level temperature in the Canadian Shield (Gula and Peltier 2012;Martynov et al 2012;Notaro et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For Nam Co, the forcing data were from the gridded China meteorological dataset developed by the hydrometeorological research group at the Institute of Tibetan Plateau Research, Chinese Academy of Sciences (ITPCAS) (Chen et al, 2011;He and Yang, 2011). The forcing variables in this dataset are the same as those for the Alaskan lake.…”
Section: Datamentioning
confidence: 99%
“…In addition to the above two categories, bulk mixed layer models have also been developed, including FLake (a relatively simple two-layer model based on the similarity theory; Mironov et al, 2010) as a typical example. Gula and Peltier (2012) and Mallard et al (2014) have coupled FLake to WRF in one-way and two-way model configurations, respectively. However, it is difficult for these oversimplified lake models to capture seasonal stratification and to accurately simulate water temperature in deep lakes.…”
Section: Introductionmentioning
confidence: 99%